1980
DOI: 10.1021/ed057pa324.4
|View full text |Cite
|
Sign up to set email alerts
|

Modern Size-Exclusion Liquid Chromatography (Yau, W. W.; Kirkland, J. J.; Bly, D. D.)

Abstract: This book represents an effort to present a complete description of the chemistry of silica and is a greatly expanded and updated version of a previous book by the same author ("The Chemistry of Silica and Silicates," Cornell University Press, 1955).The book is divided into seven chapters-The Occurrence, Dissolution, and Deposition of Silica, 115 pp.; Water Soluble Silicates, 55 pp.; Polymerization of Silica, 150 pp. ; Colloidal Silica-Concentrated Sols, 127 pp.; Silica Gels and Powders, 160 pp.; The Surface C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
3

Year Published

1985
1985
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 0 publications
1
17
0
3
Order By: Relevance
“…The procedure used was modified from that of Dean et al (8). Thus, lyophilized bovine GBM was suspended in 8 M urea/0.05 M Tris HCl, pH 7.5, containing the protease inhibitors mentioned above, by using a Potter-Elvehjem homogenizer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The procedure used was modified from that of Dean et al (8). Thus, lyophilized bovine GBM was suspended in 8 M urea/0.05 M Tris HCl, pH 7.5, containing the protease inhibitors mentioned above, by using a Potter-Elvehjem homogenizer.…”
Section: Methodsmentioning
confidence: 99%
“…The Goodpasture antigen has been isolated by using such collagenase digests and found to be contained in the NC1 globular domain (6,7). The monomeric form ofthe NC1 globule can also be prepared by collagenase digestion of collagen IV a chains isolated from GBM by reduction and alkylation of disulfide bonds under denaturing conditions (6,8). Antibodies raised against subunits of the NC1 globule (9) react only with collagen IV and can be used to identify this collagen.…”
mentioning
confidence: 99%
“…The positive cooperativity of Ca 2ϩ binding has been proposed to be a result of protein-protein interactions (23,30). Similarly, Dean et al (19,31) have shown that solubilization of SERCA1 with the nonionic detergent C 12 E 8 results in the formation of an As a first step in reaching a molecular understanding of the enzymatic differences between R. sylvatica and R. clamitans SERCA1s, we report the complete amino acid sequences for the two proteins. Comparisons between R. sylvatica, R. clamitans, and R. esculenta indicate that there are seven amino acids in SERCA1 that are unique to R. sylvatica and, therefore, may be related to the functional differences noted above (Table I).…”
Section: Discussionmentioning
confidence: 76%
“…Besides the cisand transfused bicyclic pyrimidinones with different sizes of the carbocycle (133),(2812g*116) we have synthesized and studied numerous three-ring homologues. These were differently saturated stereohomogeneous derivatives, e.g.…”
Section: Saturated Thiazolo-and Thiazin0[23-b]-quinazolinonesmentioning
confidence: 99%